Physiological impact of wearing a surgical face mask during walking in the COVID-19 pandemic - Baydil, Bilgehan; Gurses, Veli V.; Uzun, Mahmut E.; Ozcan, Neslihan; Akgül, Mustafa Ş. (Sergii Iermakov, 2021)
Background and Study Aim. Common use of surgical face masks is recommended for social and individual health due to the COVID-19 pandemic. However, there is no systematic report for responses of organism to wearing a surgical face mask during different exercises. In this context the purpose of this study was to examine the impacts of wearing a surgical face mask during a one-hour brisk walking. Material and Methods. A total of thirty male (n=16) and female (n=14) volunteers (mean age and BMI of 32±1.07 years and 25.1±0.68 kg/m2, respectively) completed the protocol. This was a multiple cross-over trial for healthy volunteers. All participants took a one-hour brisk walking with and without a surgical face mask. Specific physiological measurements (HR - heart rate; BP - blood pressure, SaO2 - arterial oxygen content) were compared before and immediately after two brisk walking. Each subject served their own control. Results. The evaluation found that there was no statistically significant difference between the mean HR and blood pressure values during the brisk walking with and without a surgical face mask, while there was a statistically significant difference in the SaO2 values on behalf of no-mask-walking (p<0.05). Conclusions. The use of surgical face masks in healthy volunteers causes a decrease in SaO2 during brisk walking. However, it does not affect the mean pulse rate and blood pressure. Although there was a statistically significant decrease in the SaO2 parameter during mask-walking, it is possible to state that brisk walking with a surgical face mask does not have a physiologically negative impact, because this decrease is in ranges that are accepted to be normal.
Keywords: covid-19; LC8-6691; GV557-1198.995; surgical face mask; brisk walking; Special aspects of education; oxygen saturation; Sports; 3. Good health